The Implications of Random Walk Hypothesis in Efforts to Increase Market Efficiency in the Stock Exchange: a Systematic Literature Review - Hamid Habbe; Mediaty Mediaty; A. Alyani Achmad; Sitti Hajerah (CV. AFDIFAL MAJU BERKAH, 2025)
The Random Walk Hypothesis implies that markets are highly efficient and that price movements of securities are unpredictable. Therefore, for investors, a passive investment approach, such as buying and holding, is more advisable than trying to find short-term profits by trying to identify patterns in price movements. However, this theory is also criticized by some who argue that markets are not always fully efficient, and that certain investor behaviors or events can produce more structured patterns in market prices. To determine the literature review on the implications of the hypothesis of random movements as an effort to improve the efficiency of the stock market. The application of Systematic Literature Review method in this study using prisma method with the help of Watase uake tools. The results showed that the random walk hypothesis phenomenon is influenced by various factors, including information asymmetry, market policies and regulations, market volality, calendar anomalies, arbitrage and market manipulation, trading technology or algorithms, and macroeconomic conditions